2021
DOI: 10.1002/ente.202100868
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of Implied and External VOC Due to Ionic Movement Explaining Transient VOC Overshoot in Perovskite Solar Cells

Abstract: An overshoot of the open‐circuit voltage (V OC) after switching off the illumination is observed for perovskite solar cells, while the simultaneously measured photoluminescence (PL) intensity decreases continuously. Similarly, a dip in the photovoltage transient is detected at the beginning of a light pulse added to a continuous bias light, while the PL increases. This decoupling of external and implied V OC (as derived from the PL data) originates from a strong gradient of the majority charge carrier quasi‐Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In a recent publication, we showed that such a decoupling between the PL intensity, i.e., quasi‐Fermi‐level (QFL) splitting or internal photovoltage (i V OC ), and the externally measured V OC originates from a strong gradient of the majority charge carrier QFL in the vicinity of a nonideal contact. [ 40 ] Supposedly this gradient occurs at the carbon contact due to an interplay between surface recombination current and conductivity limitation due to ionic space charge. The overshoot is suppressed by the introduction of a 2D perovskite EBL.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent publication, we showed that such a decoupling between the PL intensity, i.e., quasi‐Fermi‐level (QFL) splitting or internal photovoltage (i V OC ), and the externally measured V OC originates from a strong gradient of the majority charge carrier QFL in the vicinity of a nonideal contact. [ 40 ] Supposedly this gradient occurs at the carbon contact due to an interplay between surface recombination current and conductivity limitation due to ionic space charge. The overshoot is suppressed by the introduction of a 2D perovskite EBL.…”
Section: Resultsmentioning
confidence: 99%
“…Such a V OC overshooting effect has also been reported by Herterich et al during solar cell device measurements. [84] These authors suggested that due to the presence of mobile ions in the perovskite layer, a space charge layer forms between the perovskite and the contact layer. This space charge layer decreases the conductivity of the majority charge carriers, leading to a gradient of the quasi-Fermi level splitting at the contact interface.…”
Section: Methylamine-treated Samplementioning
confidence: 99%
“…The previously discussed microscopic inhomogeneity of the PEAI passivation layer and influence of the ionic space charge proposes the following mechanism for the J SC loss: under short-circuit conditions, the ions are distributed in a way that the conductivity for the electrons is rather small in the vicinity of the ETL as was shown already in our previous work. [36,38] As a consequence, many of them cannot reach those domains in the perovskite/PEAI interface within their lifetime where efficient electron extraction is possible. In contrast, with the ion distribution corresponding to open-circuit conditions, the electron conductivity increases and hence (much) more electrons can be extracted.…”
Section: Ionic Contributionmentioning
confidence: 99%
“…[16,35] Nevertheless, as perovskite solar cells are often governed by interfacial recombination, the PL intensity can remain high due to transport limitations. [36][37][38] In this work, we investigate highefficiency perovskite solar cells in p-i-n configuration with a PEAI-based 2D passivation layer as model system. With increasing thickness of the PEAI layer, an increased J SC loss is observed, while the fill factor (FF) is much less affected.…”
Section: Introductionmentioning
confidence: 99%